Addressing unmet needs in relapsed/refractory multiple myeloma: an Italian Delphi consensus on current challenges and emerging therapies - Cavo, Michele; Bringhen, Sara; Buda, Gabriele; Di Raimondo, Francesco; Musto, Pellegrino; Offidani, Massimo; Petrucci, Maria T.; Zamagni, Elena; Zambello, Renato; Berruto, Francesco; Freddi, Rachele; La Malfa, Paola (Frontiers in Oncology, 2026)
BackgroundDespite advances in treating multiple myeloma, the management of patients with relapsed or refractory disease remains a major clinical challenge. The increasing use of novel agents in frontline therapy has led to a growing population refractory to key drugs such as lenalidomide and daratumumab, resulting in limited effective options in subsequent lines. Moreover, the increasing prevalence of double-refractory cases highlights a challenge with limited evidence guiding treatment choice. In Italy, the anticipated introduction of innovative immunotherapies offers new hope, yet their real-world impact remains uncertain. This study aimed to establish expert consensus on current challenges, emerging therapies, and address unmet needs in the Italian clinical landscape.MethodsA modified Delphi process was employed to reach consensus regarding the current and future management of relapsed/refractory multiple myeloma in Italy. One hematology expert served as opinion leader, while a panel of eight experts participated in two rounds of online surveys and a final virtual consensus meeting. Panelists were blinded to others throughout the process. In each survey round, experts provided their level of agreement on statements regarding epidemiology of multiple myeloma in Italy, treatment patterns in clinical practice, and unmet needs in second and subsequent therapy lines. The final meeting allowed discussion and consolidation of responses.ResultsMost statements (28/31, 90%) achieved consensus after two Delphi rounds, while three required further discussion and agreement in the final meeting. Experts reached consensus on the epidemiology of multiple myeloma in Italy and preferred treatment patterns for relapsed/refractory disease. They consistently highlighted the limited efficacy and safety of available second- and third-line therapies for relapsed/refractory multiple myeloma, regardless of prior exposure, recognizing a substantial unmet clinical need due to the lack of satisfactory options, particularly in specific populations including double-refractory patients to lenalidomide and anti-CD38 agents. The anticipated introduction of innovative immunotherapies was identified as a promising opportunity to address these gaps and improve outcomes.ConclusionDespite multiple available agents and combinations, effective treatment of all patients with relapsed/refractory multiple myeloma remains a major unmet need. Given their distinct mechanism of action, immunotherapies hold significant potential to address this gap and improve clinical outcomes.